Global warming: Antioxidant responses to deal with drought and elevated temperature in Stylosanthes capitata, a forage legume - Borjas-Ventura, Ricardo [UNESP]; Ferraudo, Antonio Sergio [UNESP]; Martínez, Carlos Alberto; Gratão, Priscila Lupino [UNESP] (Wiley, 2020)
Drought can be more frequent and severe along with elevated temperatures (eT). To deal with the climate change impact on plants, we need to understand the plant biochemical performance. Nowadays, there is a lack of information about the antioxidant response of plants, mainly growing in field conditions and under the future climatic scenario. In this context, we carried out this experiment to analyse the antioxidant responses of the forage legume Stylosanthes capitata Vogel (in field condition) to eT and water deprivation. This work had four treatments: control, eT (+2°C above ambient canopy temperature), wS (water deprivation) and eT + wS. Temperature free-air controlled enhancement (T-FACE) system was used for warming, and samples were taken 17, 24 and 46 days after warming exposure at time periods of 6:00 a.m. and 12:00 p.m. The eT + wS treatments decreased catalase, superoxide dismutase (SOD) and ascorbate peroxidase activities, especially at 46 days. Nevertheless, glutathione (GSH) content was not modified by eT + wS treatments. Also, we determined an important inverse relation among SOD-GR-GSH and MDA-H2O2. In conclusion, combined stresses provoked detrimental effects of enzymatic antioxidant responses. Furthermore, we highlighted the importance of SOD-GR and GSH to avoid damages of reactive oxygen species in S. capitata grown under climate change. In addition, we suggest an adequate irrigation management in order to improve the antioxidant systems to face the eT, successfully; besides, we consider that the uses of tolerant cultivars are key under climate change conditions.
Keywords: biochemistry responses; combined stresses; field assessment